PERAN KOMUNIKASI PEMASARAN SOSIAL DIDALAM MERUBAH PERILAKU PENGGUNA NARKOBA DI MAKASSAR - Nieke Monika Kulsum (Jurnal Ilmu dan Budaya, 2020)
Indonesia as one of the largest population in the world have a problem with the young generation. As the future of the nation and state, certainly expected the younger generation to participate in building the society of Indonesia. Because young people are the hope of this nation as a milestone in the sustainability of future Indonesia. In this globalization era, the problems caused by young people many adverse effects and technological advances in information technology. It is an alarming one that damage morale and cause of death was drugs. Especially in big cities in Indonesia, one of which is in the city of Makassar, South Sulawesi province. According to data taken from BNNP South Sulawesi in 2015 there were about 57,000 drug users, while in the whole of South Sulawesi province there are about 162.141 people. One of the programs that run overcome this is to create a drug addiction prevention program implemented by a non-governmental foundation (NGO) YKP2N. The focus of this research question is: How and what is being done by YKP2N in conducting social marketing communications in order to change the behavior of drug users in South Sulawesi ?. While this research is to gather information on: the efforts and actions taken by YKP2N in conducting social marketing communication in changing the behavior of drug users in South Sulawesi. The concept are used, marketing communications, social marketing communications, integrated marketing communications and behavior change. The method used is descriptive qualitative. By using interviews with key informants and informant in getting the data used in the study answered questions. Also literature and documentation. From the results obtained that YKP2N, has been running a few steps in the concept of social marketing. Like the exhibition, direct marketing and more. And until these studies are reported, and these activities are still on going.